Water Extract of Dryopteris crassirhizoma Attenuates Bone Loss by Suppressing Osteoclast Differentiation and Function. (20th May 2013) - Ha, Hyunil; Shim, Ki-Shuk; Kim, Taesoo; An, Hyosun; Ma, Jin Yeul
Abstract : The rhizome of Dryopteris crassirhizoma has been used as a traditional herbal medicine for treating various inflammatory and infectious diseases such as tapeworm infestation and mumps. In the present study, we investigated the bone protective effect of water extract of the rhizome of Dryopteris crassirhizoma (WEDC). We found that WEDC inhibits osteoclast differentiation via directly acting on osteoclast precursors. In osteoclast precursors, WEDC inhibited receptor activator of nuclear factor- κ B ligand- (RANKL-) induced expression of c-Fos and nuclear factor of activated T cells cytoplasmic 1, a key downstream target of c-Fos during osteoclast differentiation. We found that WEDC inhibits RNAKL-induced activation of extracellular-regulated kinase and NF- κ B that mediates c-Fos expression and osteoclast differentiation. In addition to the inhibitory effect of osteoclast differentiation, WEDC markedly suppressed bon-resorbing activity of mature osteoclasts, which was accompanied by disruption of actin ring structure. Furthermore, administration of WEDC suppressed RANKL-induced trabecular bone loss in mice. Collectively, our results demonstrate that WEDC inhibits not only osteoclast differentiation by inhibiting RANK signaling pathways in osteoclast precursors but also bone resorption by disrupting actin ring in mature osteoclasts, thereby contributing to its protective effect on bone loss.